The Effect of Forward Leaning and Pursed Lips Breathing Exercises on The Value of Oxygen Saturation in Adult Smokers - Muhammad Nurul Amin; Erna Setiawati; Rahmi Isma Asmara Putri; Meita Hendrianingtyas (Diponegoro International Medical Journal, 2020)
Background: Smoking which is a lifestyle trend continues to increase and take its toll each year. Cigarettes have chemical compounds. Which has toxic and carcinogenic effects that can cause respiratory, cardiovascular, and other irritants. This can affect the distribution of oxygen to the body tissues. Forward leaning and PLB exercises can help maximize breathing thereby improving tissue oxygen distribution. Objective: To determine the differences in oxygen saturation of adult smokers before and after practice forward leaning and pursed lips breathing.Methods: This study used a quasi-experimental method with two group pre-post test design. The research subjects were 20 male respondents, the place of implementation at the Faculty of Medicine, Diponegoro University, Semarang. Research procedures included CKD and PLB exercises in the respondent group.Results: Analysis using the Wilcoxon test obtained significant results, with p values <0.05 on acute and chronic effects after CKD and PLB exercises were performed on 20 respondents Conclusion: A significant result in the oxygen saturation value of the group with PLB and CKD treatment with the PLB group before and after exercise on acute and chronic effects in adult smokers